A girl made of air - Hetherington, Nydia (Quercus, 2020)
"Born into a post-war circus family, our nameless star was unwanted and forgotten, abandoned in the shadows of the big top, until the bright light of Serendipity Wilson threw her into focus. Now an adult, haunted by an incident in which a child was lost from the circus, our narrator, a tightrope artiste, weaves together her spellbinding tales of circus legends, earthy magic and folklore, all in the hope of finding the child... But will her story be enough to bring the pair together again?"--Publisher.